Microstructural analysis of negative anticipatory contrast: A reconsideration of the devaluation account - Wright, Rebecca L.; Gilmour, Gary; Dwyer, Dominic M. (Learning & behavior, 2013)
An animal’s appetitive behavior is not a fixed response to current stimulation but can be affected by the anticipation of future events. For example, rats regularly given access to a moderately valued solution followed by a higher value solution (e.g., 4 % sucrose → 32 % sucrose) consume less of the initial solution than in control conditions where the initial solution is not followed by a higher value solution (e.g., 4 % sucrose → 4 % sucrose). Previous analyses have suggested that this negative anticipatory contrast effect does not depend on the “expectation” of a valuable stimulus producing a functional devaluation of a currently available stimulus of lesser value. In a within-subjects anticipatory contrast procedure, this study revealed that both consumption and the mean size of licking clusters were smaller for a 4 % sucrose solution on days when it preceded 32 % sucrose than on days when 4 % preceded 4 %. Since lick cluster size typically bears a positive monotonic relationship with the concentration of palatable solutions, this reduction is indicative of a decrease in the palatability/hedonic value of the solution subject to contrast. As such, we provide direct evidence that negative anticipatory contrast does produce a functional devaluation of the solution, thus challenging prevailing theoretical assumptions.